Fixed versus flexible – guess who wins? - Lisitsyna, Olena (Збірник наукових праць Черкаського державного технологічного університету. Серія: Економічні науки, 2015)
The article is devoted to the problem of fixed price, time and materials pricing models on outsource projects of software development. Based on real experience of big IT company there are ready solutions how to deal with that issue and make a right choice along with how to prevent unexpected budget increase on specific project. Among necessary steps to achieve this goal there are the following ones: technical specification writing with such deliverables as user stories, wires, clickable prototypes, test plan, project plan, and a detailed estimate of the project; calculating of predictable and unpredictable risks (along with definition of the ways how to do that), the work on agreements base that includes Change Order agreement. The conclusion is that good communication of these preventing steps at the very beginning of project conversations is extremely important.